On the taxonomy of Negeta semialba Hampson, 1918 with descriptions of two new Leucobaeta László, Ronkay & Witt, 2010 species (Lepidoptera, Nolidae, Nolinae) - László, Gyula M. (Zootaxa, 2022)
The taxonomic position of the West African Negeta semialba Hampson, 1918 is revised and the species is transferred from the genus Negeta Walker, 1862 of Westermanniinae to Leucobaeta László, Ronkay & Witt, 2010 of Nolinae: Leucobaeta semialba (Hampson, 1918) comb. n., based on morphological analysis. The hitherto unknown male adult and genitalia of both sexes are described and illustrated. Leucobaeta semialba is compared to the superficially similar Afrotropical Negeta mesoleuca (Holland, 1894) and N. ruficeps (Hampson, 1902); two sibling species from East Africa and Madagascar are described as new to science: L. smithi and L. malagassa spp. n. Pairwise genetic distances of COI-5P sequences between the taxa are provided.